Dynamic Governance Model Within Integrated Waste Management In Malang City: Agile People And Process In Action - Muhammad Kamil; Ali Roziqin; Yusrin Rahmawati (Universitas Muhammadiyah Yogyakarta, 2021)
As an urban area, Malang City has waste management problems, with causes ranging from governance to the lack of supporting facilities. Therefore, this article aims to discuss waste management using a dynamic governance approach. A qualitative approach was employed and aimed at providing a more nuanced narrative of how and why urban waste management is performed, alongside the involved social phenomena. The result was a dynamic governance framework in waste management practices in Malang City, including waste facilities, the development of sanitary landfill methods, and partnerships with international organizations. Although facilities, such as waste banks and Final Disposal Place (FDS), are still needed, efforts to apply agile principles with a citizen-centric approach in the development have not received great attention from the municipality. Meanwhile, household groups produce more waste due to the current condition of the city